Food Addiction in Patients with Newly Diagnosed Type 2 Diabetes in Northeast China - Yang, Fan; Liu, Aihua; Li, Yongze; Lai, Yaxin; Wang, Guixia; Sun, Chenglin; Sun, Guang; Shan, Zhongyan; Teng, Weiping (Frontiers in Endocrinology, 2017)
Abstract Aim: The aim of the study was to explore the prevalence of food addiction (FA) in individuals with newly diagnosed type 2 diabetes mellitus (T2DM) in China and to analyze risk factors of FA. Methods: A total of 624 subjects [312 individuals with newly diagnosed T2DM, 312 age-matched and body mass index (BMI)-matched healthy participants] were recruited. All participants were asked to complete the Yale Food Addiction Scale (YFAS) and received physical and lab examinations. The T2DM group was further divided into a FA group and a non-FA group. Results: Of the patients with newly diagnosed T2DM, 8.6% (27/312) met the FA diagnostic criteria proposed by the YFAS (7.6% in men and 10.1% in women, P=0.43), while 1.3% (4/312) met the criteria in the control group. Logistic regression analysis showed that FA in the T2DM group was positively related to BMI and negatively related to age. T2DM with FA had a significantly higher Uric Acid (UA) and a trend towards a lower Thyroid Stimulating Hormone(TSH) level. Conclusion: Both men and women with newly diagnosed T2DM, especially in northeast China, were more likely to suffer from FA. T2DM patients with FA were younger and had higher UA.